2013
DOI: 10.3389/fnins.2013.00188
|View full text |Cite
|
Sign up to set email alerts
|

Toward a unified biological hypothesis for the BDNF Val66Met-associated memory deficits in humans: a model of impaired dendritic mRNA trafficking

Abstract: Brain-derived neurotrophic factor (BDNF) represents promotesa key molecule for the survival and differentiation of specific populations of neurons in the central nervous system. BDNF also regulates plasticity-related processes underlying memory and learning. A common single nucleotide polymorphism (SNP) rs6265 has been identified on the coding sequence of human BDNF located at 11p13. The SNP rs6265 is a single base mutation with an adenine instead of a guanine at position 196 (G196A), resulting in the amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 82 publications
(118 reference statements)
1
37
0
1
Order By: Relevance
“…Additionally, trafficking of the BDNF 5′ UTR splice variant resulting from exon 6 is impaired in mice expressing the BDNF human variant Val66Met [81], having implications for BDNF action on the dendritic arbor. Finally, as the Val66Met mutation results in decreased transport of BDNF mRNA in the dendrites (as reviewed in [82]), and thus a disruption of the BDNF mRNA spatial code [83], it is possible that local stimulation of the dendritic arbor by BDNF-coated beads may alleviate some of the issues caused by this dysregulation in BDNF mRNA transport. Thus, expression of specific BDNF mRNAs is crucial for the proper regulation of dendritogenesis and other cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, trafficking of the BDNF 5′ UTR splice variant resulting from exon 6 is impaired in mice expressing the BDNF human variant Val66Met [81], having implications for BDNF action on the dendritic arbor. Finally, as the Val66Met mutation results in decreased transport of BDNF mRNA in the dendrites (as reviewed in [82]), and thus a disruption of the BDNF mRNA spatial code [83], it is possible that local stimulation of the dendritic arbor by BDNF-coated beads may alleviate some of the issues caused by this dysregulation in BDNF mRNA transport. Thus, expression of specific BDNF mRNAs is crucial for the proper regulation of dendritogenesis and other cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…PCR products were visualized on a 1.2% agarose gel. The Val66Met polymorphism was subsequently determined via an established pyrosequencing protocol with oligo sequencing 5Ј-GCTGACACTTTCGAACA-3Ј (Baj et al, 2013). The analyzed sequence was as follows: CA/GTGATAGAA-GAG.…”
Section: Discussionmentioning
confidence: 99%
“…In Caucasians, 25-35% of the population carries a valine (Val) to methionine (Met) substitution at codon 66 (referred to as Met carriers) and has reduced activity-dependent BDNF secretion compared with homozygous BDNF Val allele carriers (referred to as Val/Val carriers; Egan et al, 2003). Several studies have linked reduced BDNF secretion in Met carriers with lower synaptic plasticity and poorer memory (Baj et al, 2013), although significant inconsistencies exist (Mandelman and Grigorenko, 2012). In comparison with Val/Val carriers, it was suggested that Met carriers experience growing impairment on memory tasks as they age (Kennedy et al, 2015), making the aging population particularly appealing to understanding how the BDNF Met allele affects memory.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, this potential mechanism is reinforced by the recordings from ne-tBDNF distinct neurons and by the detected colocalization of TrkB receptors and VGAT positive presynaptic terminals. An impairment of this mechanism has been associated with memory deficits in mice and humans [93]. Another mechanism which may underlay the differences observed between exogenous and endogenous long-term BDNF application, may involve the ability of glial cells, in particular astrocytes, to uptake circulating BDNF [94,95], thus leading to different effects.…”
Section: Discussionmentioning
confidence: 99%